Investigation of the Molecular Mechanisms of the Eukaryotic Cytochrome-c Maturation System - Silva, Ana V. (2022)
Funding Information: Financial support was provided by European EC Horizon 2020 TIMB3 (Project 810856). Financial support was also provided by Project MOSTMICRO-ITQB with refs UIDB/04612/2020 and UIDP/04612/2020. Fundação para a Ciência e a Tecnologia (FCT) Portugal is also acknowledged for funding through project PTDC/BIA-BQM/30176/2017, and through SFRH/BD/129067/2017 to A.V.S. Funding Information: Funding: Financial support was provided by European EC Horizon2020 TIMB3 (Project 810856). Financial support was also provided by Project MOSTMICRO-ITQB with refs UIDB/04612/2020 and UIDP/04612/2020. Fundação para a Ciência e a Tecnologia (FCT) Portugal is also acknowledged for funding through project PTDC/BIA-BQM/30176/2017, and through SFRH/BD/129067/2017 to A.V.S. Publisher Copyright: © 2022 by the authors. Licensee MDPI, Basel, Switzerland.